Hyphenated hydrology: Interdisciplinary evolution of water resource science. Issue 4 (10th April 2017) - McCurley, Kathryn L.; Jawitz, James W.
Abstract: Hydrology has advanced considerably as a scientific discipline since its recognized inception in the mid‐twentieth century. Modern water resource related questions have forced adaptation from exclusively physical or engineering science viewpoints toward a deliberate interdisciplinary context. Over the past few decades, many of the eventual manifestations of this evolution were foreseen by prominent expert hydrologists. However, their narrative descriptions have lacked substantial quantification. This study addressed that gap by measuring the prevalence of and analyzing the relationships between the terms most frequently used by hydrologists to define and describe their research. We analyzed 16, 591 journal article titles from 1965–2015 in Water Resources Research, through which the scientific dialogue and its time‐sensitive progression emerged. Our word frequency and term cooccurrence network results revealed the dynamic timing of the lateral movement of hydrology across multiple disciplines as well as the deepening of scientific discourse with respect to traditional hydrologic questions. The conversation among water resource scientists surrounding the hydrologic subdisciplines of catchment‐hydrology, hydro‐meteorology, socio‐hydrology, hydro‐climatology, and eco‐hydrology gained statistically significant momentum in the analyzed time period, while that of hydro‐geology and contaminant‐hydrology experienced periods of increase followed by significant decline. This study concludes that formerly exotic disciplines can potentially modify hydrology, prompting new insights and inspiring unconventional perspectives on old questions that may have otherwise become obsolete. Key Points: Hydrology is becoming increasingly interdisciplinary over time The terms used in publication titles reveal dialogue regarding pertinent issues and can be used to predict discipline evolution Hydrology can best address the holistic nature of water resource issues through multifaceted interfaces with other disciplines